Nanomedicines against Chagas disease: A critical review - Morilla, María José (2024)
Chagas disease (CD) is the most important endemic parasitosis in South America and represents a great socioeconomic burden for the chronically ill and their families. The only currently available treatment against CD is based on the oral administration of benznidazole, an agent, developed in 1971, of controversial effectiveness on chronically ill patients and toxic to adults. So far, conventional pharmacological approaches have failed to offer more effective and less toxic alternatives to benznidazole. Nanomedicines reduce toxicity and increase the effectiveness of current oncological therapies. Could nanomedicines improve the treatment of the neglected CD? This question will be addressed in this review, first by critically discussing selected reports on the performance of benznidazole and other molecules formulated as nanomedicines in in vitro and in vivo CD models. Taking into consideration the developmental barriers for nanomedicines and the degree of current technical preclinical efforts, a prospect of developing nanomedicines against CD will be provided. Not surprisingly, we conclude that structurally simpler formulations with minimal production cost, such as oral nanocrystals and/or parenteral nano-immunostimulants, have the highest chances of making it to the market to treat CD. Nonetheless, substantive political and economic decisions, key to facing technological challenges, are still required regarding a realistic use of nanomedicines effective against CD.